Las veedurias ciudadanas como garante de los recursos públicos en Colombia a la Luz de la Ley 850 de 2003 (2018)
With the entry into force of the Political Constitution of 1991, through which Colombia calls itself a social State of Law, unitary Republic and participatory democracy, the Citizen Veciendas which ensure Citizen Participation, increasing the confidence of the inhabitants of the national territory and the positive results of public policies generated by the State; it is necessary to have a good planning and control by means of which one can identify with the problems that these families can generate, in order to correct and find the best solutions for the citizenship, since what is sought is the confidence of the citizens and for this, it is necessary that the State works and strives to achieve its goals, through the principle of transparency, access to information, opportunity and quality